Detection and Determination of Bacillus cereus in Cooked Rice and Some Types of Spices with Ribosomal 16SrRNA gene Selected from Iraqi Public Restaurants - Jessim, Ahmed Ibrahim; Fakhry, Saad Sabah; Alwash, Samarah Jafar (International Journal of Bio-resource and Stress Management, 2017)
Spices can be considered as one of the sources of bacterial food pollution because of spices multiuse, in addition to the manufacturing processing and use, also they considered as one of food contamination reason due to the quantity of microorganisms like spore forming Bacteria such as Bacillus cereus. These road shape bacteria and its spores can move by air fast and easy, B. cereus is indicated to Diarrheal syndrome which linked to Non-hemolytic enterotoxin (NHE). Different kinds of 40 samples of spices was tested and 24 samples of cooked rice which considered as traditional food for wide stratum of Iraqi people from public restaurants located in Baghdad city, spices samples continued high number of B. cereus in spice (Fennel) in high number about 44×105 Cfu g-1 in addition to sample of spice (Kebab) 39×105 Cfu g-1 these numbers are high and unacceptable. As for samples of cooked rice have a fewer numbers of bacteria except one sample had record 4.9×103 Cfu g-1 in winter. But in summer samples had a higher numbers of B. cereus than winter period, some samples continued 14.4×105, 12.3×105 and 1.15×105 Cfu g-1, these numbers are high and in this case can cause the diarrheal syndrome. Due to morphological and biochemical studies, these isolates are belong to B. cereus. After proceeding molecular biology and Polymerase Chain Reaction (PCR) for Ribosomal 16SrRNA gene-speciﬁc for these isolates, where tests are positive for 15 isolates of 64 selected isolates from spices and cooked rice, results showed these isolates are toxigenic